2014
DOI: 10.1063/1.4883757
|View full text |Cite
|
Sign up to set email alerts
|

Single trap dynamics in electrolyte-gated Si-nanowire field effect transistors

Abstract: Liquid-gated silicon nanowire (NW) field effect transistors (FETs) are fabricated and their transport and dynamic properties are investigated experimentally and theoretically. Random telegraph signal (RTS) fluctuations were registered in the nanolength channel FETs and used for the experimental and theoretical analysis of transport properties. The drain current and the carrier interaction processes with a single trap are analyzed using a quantum-mechanical evaluation of carrier distribution in the channel and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 63 publications
0
26
0
Order By: Relevance
“…2. Distribution of the carrier profiles, calculated using a quantum approach, 13 is plotted in Fig. 3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2. Distribution of the carrier profiles, calculated using a quantum approach, 13 is plotted in Fig. 3.…”
Section: Resultsmentioning
confidence: 99%
“…They demonstrate that the slope of the electron capture time dependence on gate voltage is equal to (À1), which fully corresponds to the measured data. 13 Theoretical curves (Fig. 4) were calculated using a quantum approach for capture time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These materials are very sensitive to surface charge because of high surface-to-bulk ratio. [4][5][6] Selective biochemical sensing has been successfully demonstrated using CNTs [7][8][9] and Si nanowires [10][11][12] . In this paper, we investigate a GaAs-based nanowire field-effect transistor (FET) for detection of the static and dynamic charge state of the molecule.…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon of the low-frequency (LF) fluctuation of electric current in semiconductors and semiconductor devices is the subject of investigations by many researchers and engineers. [26][27][28][29][30][31] Studies have shown that the behavior and magnitude of LF noise in devices based on nanosize silicon structures differs essentially from the noise in devices based on crystalline silicon.…”
Section: Signal-to-noise Ratio (Snr) and Ph Sensitivitymentioning
confidence: 99%